2001
DOI: 10.1111/j.1525-1497.2001.01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Managed care, professional autonomy, and income

Abstract: Our results suggest that when managed care (or other influences) erode professional autonomy, the result is a highly negative impact on physician career satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(65 citation statements)
references
References 28 publications
5
58
0
2
Order By: Relevance
“…On the one hand, provider satisfaction with autonomy has been shown to decrease with higher penetration of managed care in a given location (Baker and Cantor 1993;Collins et al 1997;Hadley and Mitchell 2002;Murray et al 2001;Warren et al 1999), perhaps as a result of providers becoming more accountable to external controls (Mechanic 2003;Warren et al 1999). Similarly, physicians in states with higher HMO penetration are less likely to say they have freedom in caring for patients (Burdi and Baker 1997;Hadley et al 1999;Stoddard et al 2001), and inpatient mental health professionals are more likely to report a lack of authority and responsibility than are those in community-based settings (Marriott et al 1994;Reid et al 1999). …”
Section: Autonomymentioning
confidence: 93%
See 2 more Smart Citations
“…On the one hand, provider satisfaction with autonomy has been shown to decrease with higher penetration of managed care in a given location (Baker and Cantor 1993;Collins et al 1997;Hadley and Mitchell 2002;Murray et al 2001;Warren et al 1999), perhaps as a result of providers becoming more accountable to external controls (Mechanic 2003;Warren et al 1999). Similarly, physicians in states with higher HMO penetration are less likely to say they have freedom in caring for patients (Burdi and Baker 1997;Hadley et al 1999;Stoddard et al 2001), and inpatient mental health professionals are more likely to report a lack of authority and responsibility than are those in community-based settings (Marriott et al 1994;Reid et al 1999). …”
Section: Autonomymentioning
confidence: 93%
“…Income is a major predictor of work satisfaction (Cashman et al 1990;Martin and Schinke 1998;Murray et al 2001;Pathman et al 2002;Schulz et al 1997;Stoddard et al 2001). This dimension is usually defined as ''satisfaction with total compensation: direct pay, financial or nonfinancial fringe benefits, and future prospects for financial security'' (Konrad et al 1999(Konrad et al , p. 1176.…”
Section: Satisfaction With Compensationmentioning
confidence: 96%
See 1 more Smart Citation
“…Degree of autonomy found to be significantly related to career satisfaction is similar to the findings of Stoddard et al and the study by Society of General Internal Medicine (SGIM), the latter study reported that primary care physicians and specialist who rated their autonomy lower were more likely to report decreased satisfaction with their careers over a four year period. 12,13 Two studies done in developing countries one in Saudi Arabia among primary health care physicians showed 64.2% of doctors to be satisfied with autonomy and another in Karachi, Pakistan showed 54% of doctors to be satisfied with autonomy. 14,15 With regards rate of promotion 33.3% were neutral, 22.1% dissatisfied and 16.7% very dissatisfied.…”
Section: Discussionmentioning
confidence: 99%
“…This new system was planned based on the concept of diagnosis-related groups (DRG)/PPS in the USA [1]. The DRG/PPS is a per-case payment system, and displays effects of shortening length of hospital stay (LOS), reducing total medical costs, and standardizing medical care [2][3][4]. The DPC in Japan was planned to manage the total medical costs, and adopted as a per-day payment system but not as a per-case payment system [1,4].…”
Section: Introductionmentioning
confidence: 99%